Probabilistic Modelling of Replica Divergence - Rowstron, Ant; Lawrence, N. D.; Bishop, Christopher (HotOS 2001, 2001)
It is common in distributed systems to replicate data. In many cases this data evolves in a consistent fashion and this evolution can be modelled. A probabilistic model of the evolution allows us to estimate the divergence of the replicas and can be used by the application to alter its behaviour, for example to control synchronisation times, to determine the propagation of writes, and to convey to the user information about how much the data may have evolved. In this paper, we describe how the evolution of the data may be modelled and outline how the probabilistic model may be utilised in various applications, concentrating on a news database example.